Tính A=7^1+7^2+7^3+...+7^2011
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=\dfrac{4}{5}\cdot\dfrac{7}{3}\cdot\dfrac{3}{7}\cdot\dfrac{5}{4}+2011=2011+1=2012\)
b: \(=\dfrac{1}{3}\cdot\dfrac{9}{7}\cdot\dfrac{7}{9}=\dfrac{1}{3}\)
\(B=\left(1-\frac{1}{7}\right)\left(1-\frac{2}{7}\right)\left(1-\frac{3}{7}\right)...\left(1-\frac{2011}{7}\right)\)
\(B=\frac{6}{7}.\frac{5}{7}.\frac{4}{7}....\frac{-2004}{7}\)
Còn lại bạn tự tính đi.
\(A=\dfrac{7}{10}+\dfrac{7}{10^2}+\dfrac{7}{10^3}+...+\dfrac{7}{10^{2011}}\)
\(\Rightarrow10A=7+\dfrac{7}{10}+\dfrac{7}{10^2}+...+\dfrac{7}{10^{2010}}\)
\(\Rightarrow10A-A=7+\dfrac{7}{10}+\dfrac{7}{10^2}+...+\dfrac{7}{10^{2010}}-\left(\dfrac{7}{10}+\dfrac{7}{10^2}+\dfrac{7}{10^3}+...+\dfrac{7}{10^{2011}}\right)\)
\(\Rightarrow9A=7-\dfrac{7}{10^{2011}}\)
\(\Rightarrow A=\dfrac{7}{9}.\left(1-\dfrac{1}{10^{2011}}\right)\)
A = 71 + 72 + 73 + ..... + 72011
=> 7A = 72 + 73 + 74 + ..... + 72012
=> 7A - A = ( 72 + 73 + 74 + ..... + 72012 ) - ( 71 + 72 + 73 + ..... + 72011 )
=> 6A = 72 + 73 + 74 + ..... + 72012 - 71 - 72 - 73 - ..... - 72011
=> 6A = 72012 - 71
=> A = \(\frac{7^{2012}-7}{6}\)
Cảm ơn ạ